A KRAS wild type mutational status confers a survival advantage in pancreatic ductal adenocarcinoma - Windon, Annika L. (J Gastrointest Oncol, 2018)
BACKGROUND: The KRAS oncogene is a driver mutation and is present in greater than 90% of pancreatic ductal adenocarcinomas (PDAC). A subset of these tumors, however, do not harbor mutations in KRAS (wild type KRAS). Studies have shown that patients with mutated KRAS have a poorer survival on first-line gemcitabine-based chemotherapy compared to wild type KRAS. In this study, we examined a cohort of patients with PDAC at our institution who were either wild type or mutant for the KRAS gene and assessed for differences in survival and response to different chemotherapeutic regimens. METHODS: We examined clinical records of patients treated at the Abramson Cancer Center of the University of Pennsylvania from 2013 to 2017. Patients with a pancreatic mass and a histologic diagnosis of pancreatic or pancreaticobiliary adenocarcinoma were identified. Thirty-nine patients with PDAC who underwent tumor sequencing at Penn Medicine’s Center for Personalized Diagnostics (CPD) were selected for further study. Twelve patients were identified whose tumors were KRAS wild type. Twenty-seven patients with PDAC whose tumors harbored KRAS mutations were selected as controls (KRAS mutant). RESULTS: We noted a longer overall survival (OS) among KRAS wild type patients compared to KRAS mutant patients (P=0.026). This was independent of the age at diagnosis, patient gender, stage of diagnosis, tumor morphology, mismatch repair (MMR) status, and chemotherapeutic regimen. CONCLUSIONS: Similar to previously reported studies, PDAC with a KRAS wild type mutational profile has a better prognosis with a longer OS. This improved prognosis is independent of the protocol utilized in therapy for these patients. Our findings suggest that future clinical trials in pancreatic cancer should take into consideration the presence of KRAS mutations in their pre-planned analysis when assessing the efficacy of a novel therapeutic approach. This may be a crucial factor in trial concepts and outcomes.